Determinants of external debt in Malaysia / Zahiratul Nazura Abdul Kadir - Abdul Kadir, Zahiratul Nazura (Faculty of Business Management, 2017)
It is difficult for a developing country to support itself with only domestic financial resources because these resources are limited. So, they tend to borrow from external resources to help them in enhancing their economies. However, borrowing from other foreign countries can be one of the main problems faced by developing countries. A major obstacle to the continued capital acquisition and future economic growth, the debt burden is now one of the main concerns in international affairs. Many lesser-developed countries (LDCs) such as Myanmar and Bangladesh, today simply cannot repay these debts, without the assistance of developed countries (DCs). It is said that extra and excess portion of external borrowings more than the favorable level will contribute negatively to the country's economy instead of the collected amount of international debt helps in developing their economic growth up to an ideal level. The purpose of this paper is to examine the determinants of using external debt for Malaysia. Malaysia is chosen because this country is one of the less-developed countries that use external debt to enhance their economies. This paper wants to investigate the factor that most enhancing the external borrowings in Malaysia and why it encourages the external debt to increase. This study use annual time series data for the period 1987-2016 on debt composition and run regressions of Gross Domestic Product (GDP), inflation, trade openness, interest rate and savings gap. This paper find that the GDP, inflation, interest rate and savings gap are consistently significant determinants composition of external debt. While trade openness has negative relationship with external debt but not significant at required level of significance. Consistent with my prediction, GDP and inflation are found to have a significant positive impact on external debt. From the results obtained, it is also suggested that increase in interest rate and savings gap can promote external debt. On the other hand, GDP and inflation appear to discourage external debt.